KEBUTUHAN DAN PERMINTAAN TERHADAP LAYANAN KESEHATAN MATA: SEBUAH SURVEI DARI PENDUDUK SURABAYA - Umi Nur Khasanah (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2018)
Healthcare institutions should take into account the needs of the community for the servicesprovided to be effective. The research aims to find out the needs and needs of the public on eye healthservices in Surabaya. A survey involved 59 respondents (from Wonokromo, Gayungsari, Jemursari,and Darmahusada) in May of 2017. The research instrument was a questionnaire. Data analysisusing descriptive statistical test. The research indicates that respondents need eye health servicesinclude good and professional services (27.10%), friendly human resources (32.20%), completelaboratory (39.00%), information system (44.10%), willingness to use (79.70%), good service system(37.30%), unreliable human resources and cost and distance factors respectively 28.80%, staffcounseling (54.20%), treatment (76, 30%), puskesmas (30.50%), clinics (16.90%), taking medicine(36.00%), Eye Hospital in Undaan (37.00%), close to home (20.00%). The study recommends thatsurvey results can be used as a reference for hospital management in developing eye health servicesin line with community expectations.